Standardization procedure to provide a unified multi-method elemental compositional dataset, application to ferruginous colouring matters from Namibia. (June 2022) - Mauran, Guilhem; Caron, Benoit; Beck, Lucile; Détroit, Florent; Noûs, Camille; Tombret, Olivier; Pleurdeau, David; Bahain, Jean-Jacques; Lebon, Matthieu
Graphical abstract: Highlights: Characterization of Namibian geological ferruginous colouring matter through ICP-OES/ICP-MS, PIXE and XRF. Use of standardization procedure to provide a unified multi-analytical compositional dataset. Demonstrate possibility of multi-analytical provenance of Namibian ferruginous colouring matters. Paves the way for robust multi-analytical provenance studies of archaeological materials. Abstract: Curation of archaeological materials often leads to carrying out multi-analytical methodologies that combine non-invasive and invasive elemental analyses. Such materials are often analysed with different techniques. It results in the production of complementary but apparently non-compatible compositional datasets that cannot be easily compared. In the present paper, we propose to compare results acquired on geological ferruginous colouring matters from Namibia with analytical techniques (X-Ray Fluorescence spectrometry (XRF), Proton-Induced-X-ray Emission spectrometry (PIXE), Inductively Coupled Plasma coupled to Optical Emission spectrometry (ICP-OES) and Inductively Coupled Plasma coupled to Mass Spectrometry (ICP-MS)). We aim to provide a unified elemental dataset about these ferruginous colouring matters, usually referred to as "ochre" in archaeology. Analysed geological samples come from three distinct tectonostratigraphic zones of Namibia surveyed in the frame of rock art research. When compared directly, three of the four datasets obtained from these measurements appear as non-compatible because of the inter-equipment variability. However, through a simple standardization procedure, we demonstrate that it is possible to unify these datasets. This procedure minimizes the inter-equipment variability, making the inter-zones of provenance predominant and allowing distinctions of the samples according to their sole origin. Beyond shedding new light on the possibility to compare different elemental analytical techniques, this procedure paves the way for complementary multimodal studies of ferruginous colouring matters.